The autonomy of higher education institutions based on the constitution of the Republic of Poland and the Act on Higher Education and Science - Zbarachewicz , Beata (Prawo Kanoniczne, 2024)
The author analyzes the legal institution of university autonomy, which is guaranteed in the Constitution of the Republic of Poland and the Act on Higher Education and Science. This autonomy is divided into several aspects and includes, among others: territorial autonomy, financial autonomy, institutional autonomy, and autonomy in conducting scientific activities and publishing their results. The legal and dogmatic analysis is accompanied by examples and historical and legal elements.